Intestine Suture in Polluted Media - Uturbey, Judith; Veroli, Antonio; Zinno, Alberto; Sorondo, Mario; Rodríguez, Horacio; Gerard, Julio; La piedra, Antonio; Giordano, Pablo (Cirugía del Uruguay, 1980)
Report on performance of digestive sutures of small intestine in rats, in polfuted media.